2023
DOI: 10.3389/fncel.2022.1067365
|View full text |Cite
|
Sign up to set email alerts
|

Changing subplate circuits: Early activity dependent circuit plasticity

Abstract: Early neural activity in the developing sensory system comprises spontaneous bursts of patterned activity, which is fundamental for sculpting and refinement of immature cortical connections. The crude early connections that are initially refined by spontaneous activity, are further elaborated by sensory-driven activity from the periphery such that orderly and mature connections are established for the proper functioning of the cortices. Subplate neurons (SPNs) are one of the first-born mature neurons that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 214 publications
(378 reference statements)
0
5
0
Order By: Relevance
“…The auditory cortex (ACtx) is responsible for central sound processing. The SpNs in the ACtx respond to sounds and SpN circuits can be shaped by early auditory and visual experience (Meng et al, 2021;Mukherjee & Kanold, 2023;Mukherjee et al, 2022;Wess et al, 2017); thus, SpNs might play a crucial role in cortical circuit development and cortical processing before and after the presence of peripheral stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The auditory cortex (ACtx) is responsible for central sound processing. The SpNs in the ACtx respond to sounds and SpN circuits can be shaped by early auditory and visual experience (Meng et al, 2021;Mukherjee & Kanold, 2023;Mukherjee et al, 2022;Wess et al, 2017); thus, SpNs might play a crucial role in cortical circuit development and cortical processing before and after the presence of peripheral stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The auditory cortex (ACtx) is responsible for central sound processing. The SpNs in the ACtx respond to sounds and SpN circuits can be shaped by early auditory and visual experience (Meng et al., 2021; Mukherjee & Kanold, 2023; Mukherjee et al., 2022; Wess et al., 2017); thus, SpNs might play a crucial role in cortical circuit development and cortical processing before and after the presence of peripheral stimuli. Previous studies in the ACtx showed that the distinct spatial intracortical connectivity of SpNs changes during the first two postnatal weeks (PNWs) in mice (Meng et al., 2014; Viswanathan et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interference with the cellular mechanisms involved in immature neural activity generation, through the administration of volatile anesthetics for general anesthesia, results in neuronal apoptosis in the developing nervous system [ 23 , 24 , 25 , 26 ]. Modulation of immature neuronal activity by sensory deprivation during the late in utero or early postnatal period results in alterations to cortical map development in the sensory systems ([ 27 , 28 , 29 , 30 , 31 ]; see [ 32 ], for review). It is arguably the crucial supracellular mechanism of the development of the brain’s diverse functional organization, and modulation of it affects the development of brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, peripheral insult during the precritical period intramodally alters circuit connectivity of the earlier born subplate neurons (SPNs) (Meng et al, 2021; Mukherjee et al, 2021). SPNs are the first targets of thalamocortical inputs before they innervate L4 neurons at the onset of the critical period (Barkat et al, 2011; Friauf et al, 1990; Friauf & Shatz, 1991; Herrmann et al, 1994; Higashi et al, 2002; Molnar et al, 2003; Mukherjee & Kanold, 2022; Zhao et al, 2009). They are essential for the development of thalamocortical and corticocortical connections as well as patterning of the ocular dominance columns and barrels (Ghosh et al, 1990; Ghosh & Shatz, 1992, 1993; Kanold et al, 2003; Kanold & Luhmann, 2010; Kanold & Shatz, 2006; Molnar et al, 2020; Tolner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%